Itching sensation in psoriatic patients and its relation to body mass index and IL-17 and IL-31 concentrations - Czarnecka-Operacz, Magdalena; Polańska, Adriana; Klimańska, Magdalena; Teresiak-Mikołajczak, Ewa; Molińska-Glura, Marta; Adamski, Zygmunt; Jenerowicz, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : According to available data, pruritus is a common symptom of psoriasis, however its characteristics and pathogenesis are not clearly understood. Aim : The main aim of this study was to assess itching sensation among patients suffering from psoriasis, including its incidence and severity. All factors triggering and worsening pruritic symptoms were also carefully analyzed. The authors assessed the relationship of itch with body mass index (BMI) and severity of disease. Moreover, serum levels of interleukin 17 (IL-17) and IL-31 were analyzed in relation to Psoriasis Activity and Severity Index, BMI and severity of pruritus. Material and methods : The study group consisted of 60 patients with plaque-type psoriasis. Analysis of impact of pruritus on the quality of life and worsening factors was based on the questionnaire. The severity of pruritus was assessed with the use of two independent scales. Serum IL-17 and IL-31 levels were measured in 30 patients suffering from psoriasis and in 10 healthy controls using immunoassay tests. Results : 88.3% of analyzed patients complained of itch and the most common factor which exacerbated pruritus was stress (39.6%). Pruritus in psoriasis was independent of gender, illness duration and extent of skin lesions. The average intensity of pruritus was assessed as moderate and did not correlate significantly with BMI level, IL-17 and IL-31. Conclusions : Since the pathogenesis of pruritus in psoriasis is not fully understood, further investigation in this area needs to be conducted. Pruritus may be considered as a characteristic feature of psoriasis and, besides the skin lesions, should be a target in dermatological treatment to improve patient’s quality of life.